Experimental investigation of grooving method in seismic retrofit of beam-column external joints without seismic details using CFRP sheets. (December 2021) - Davodikia, Behzad; Saghafi, Mohammad Hossein; Golafshar, Ali
Abstract: The experience of past earthquakes has shown that the beam to column joints in moment frames is one of the key members in the path of lateral load transfer and their weak performance causes the destruction of the whole structure. The use of FRP composites in strengthening and repairing these members as an effective solution has a special place in the construction industry. However, the separation of FRP composites from the concrete surface has become the biggest challenge facing researchers. In the present study, the grooving method has been used to install CFRP composites and the ability of this method to delay or eliminate the separation of FRP composites in shear strengthening of reinforced concrete beam-column joints has been investigated. In this paper, four external concrete beam-column joints with a scale of 1/2 have been made in the laboratory. There are two specimens as controls, one of which has special seismic details in accordance with ACI regulations and the other specimen does not have seismic details. The two retrofitted specimens also lack seismic details, and CFRP composites are employed for the retrofit. In one of the retrofitted specimens, CFRP composites are installed on the concrete surface in the usual way, and in another specimen, CFRP composites are installed on the concrete surface by the grooving method. The specimens are subjected to cyclic loading with incremental amplitude. The results were evaluated by comparing hysteresis curves, envelope curves, energy dissipation, stiffness reduction and cracking pattern. The results show that the applied method eliminates the separation phenomenon and a significant increase in bearing capacity, ductility and energy dissipation was observed.